Tanabe Hajime and the Kyoto School : self, world, and knowledge - Morisato, Takeshi (London, England : Zed Books, 2021)
"This introduction to Tanabe Hajime (1885-1962), the critical successor of the "father of contemporary Japanese philosophy" Nishida Kitaro (1870-1945), focuses on Hajime's central philosophical ideas and perspective on "self," "world," "knowledge," and the "purpose of philosophizing". Exploring his notable philosophical ideas including the logic of species, metanoetics, and philosophy of death, it addresses his life-long study of the history of Western philosophy. It sets out his belief that Western framework of thinking is incapable of giving sufficient answers to the philosophical questions concerning the self and the world together and discusses the central ideas he developed while working in Eastern traditions such as Confucianism and Daoism. Featuring comprehensive further reading lists, discussion questions and teaching notes, this is an ideal introductory guide to Tanabe Hajime suitable for anyone interested in Japanese and World philosophy, as well as the development of the Kyoto School"--
Introduction -- 1. Species and The History of Western Philosophy -- 2. Metanoesis and the Fundemental Problems of Philosophy -- 3. Absolute Dialectic -- 4. Philosophy of Death Glossary Further Reading Annotated Bibliography Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Tanabe, Hajime, -- 1885-1962.; Kyoto school; Non-Western philosophy; Electronic books